Neonatal Cholestasis: A Red Alert for the Jaundiced Newborn - Dinesh Pashankar; Richard A Schreiber (Canadian Journal of Gastroenterology)
Neonatal jaundice may indicate cholestasis rather than a benign, physiological condition. Any four-week-old newborn with persistent jaundice should have a fractionated bilirubin screen to determine whether the hyperbilirubinemia is unconjugated. Conjugated hyperbilirubinemia, a hallmark of neonatal cholestasis, is pathological and requires further investigation. These infants need prompt diagnosis, early intervention and careful follow-up to ensure continued growth and development. Recent progress in the physiology of bile flow is reviewed, and the evaluation and management of neonatal cholestasis are summarized. Further advances in delineating the cellular and molecular processes that regulate bile acid metabolism in both health and disease will lead to a greater understanding of the conditions causing neonatal cholestasis. Unravelling the etiopathogenesis of these neonatal cholestatic disorders will allow the development of novel diagnostic and therapeutic interventions that ultimately will effectuate the prognosis for these young patients.